Adopting big data to create an “outside-in” global perspective of Guanxi - Lee, Liane WY; Sharma, Piyush; Barnes, Bradley R (Elsevier, 2021)
Previous research on the Chinese notion of guanxi has tended to use descriptive approaches to study its prevalence and influence on business and Chinese consumers. Relatively less research has focused on perceptions of guanxi in other parts of the world. This paper addresses this important research gap through adopting an “outside-in” global perspective using big data. In particular, the study draws on 162 million guanxi-related news articles during 2017–2020 extracted from the Global Database of Events, Language and Tone (GDELT), an open-source, real-time current affairs repository of online news and event metadata. The findings reveal that guanxi is heavily influenced by geopolitical and public health issues. The study also discovered a major contrast in the overall tone between China, being slightly positive, and the US and Germany, being largely negative, with the association varying according to changes in the marketing ecosystem.